Regression Discontinuity Evidence on the Effectiveness of the Minimum Legal E-cigarette Purchasing Age - Jeff DeSimone; Daniel Grossman; Nicolas R. Ziebarth (Institute of Labor Economics (IZA), 2022)
Increases in youth vaping rates and concerns of a new generation of nicotine addicts recently prompted an increase in the federal minimum legal purchase age (MLPA) for tobacco products, including e-cigarettes, to 21 years. This study presents the first regression discontinuity evidence on the effectiveness of e-cigarette MLPA laws. Using data on 12th graders from Monitoring the Future, we obtain robust evidence that federal and state age-18 MLPAs decreased underage e-cigarette use by 15–20% and frequent use by 20–40%. These findings suggest that the age-21 federal MLPA could meaningfully reduce e-cigarette use among 18–20-year-olds.
Keywords: I12; I18; H51; H75; 330; e-cigarettes; minimum legal purchase age (MLPA); Monitoring the Future; regression discontinuity; vaping